2000
DOI: 10.1016/s0375-9601(00)00441-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantum approach to static games of complete information

Abstract: We extend the concept of a classical two-person static game to the quantum domain, by giving an Hilbert structure to the space of classical strategies and studying the Battle of the Sexes game. We show that the introduction of entangled strategies leads to a unique solution of this game.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
428
2
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(447 citation statements)
references
References 3 publications
4
428
2
5
Order By: Relevance
“…Thus this protocol would not reproduce the classical game when the phases are set to zero. So instead we follow [9] and suppose the initial state is already in the maximally entangled state:…”
Section: A Quantum Parrondo Gamementioning
confidence: 99%
“…Thus this protocol would not reproduce the classical game when the phases are set to zero. So instead we follow [9] and suppose the initial state is already in the maximally entangled state:…”
Section: A Quantum Parrondo Gamementioning
confidence: 99%
“…Marinatto and Weber extend the concept of a classical two-person static game to the quantum domain, by giving an Hilbert structure to the space of classical strategies and investigating the Battle of the Sexes game. They show that the introduction of entangled strategies leads to a unique solution of this game [18] . Quantum Cournot's duopoly are introduced by Li H et al Li Y et al, Zhou J et al Some novel features in the quantum Cournot's duopoly are observed, which are completely due to quantum entanglement.…”
Section: A the Main Classical Game Models And Its Quantum Counterpartmentioning
confidence: 99%
“…The expected payoff for the each of the classical cheats is consequently 3 16 . For the quantum players sharing the singlet state Eq.…”
Section: Quantum and Classical Coalitionsmentioning
confidence: 99%